Marine Isotope Stage 3 paleotemperature inferred from reconstructing the Die Shan ice cap, northeastern Tibetan Plateau. Issue 2 (15th February 2018) - Cui, Hang; Wang, Jie; Yu, Beibei; Hu, Zhenbo; Yao, Pan; Harbor, Jonathan M.
Abstract: Glacial extent mapping and dating indicate that the local last glacial maximum (LLGM) of the northeastern Tibetan Plateau occurred during mid-Marine Isotope Stage (MIS) 3. This is asynchronous with the global last glacial maximum (LGM) that occurred during MIS 2. The causes underlying this asynchronicity are the subject of ongoing debate, and paleoclimatic reconstructions are a key to advancing understanding of the climatic influence on the spatial and temporal patterns of paleoglaciation. We used multiple methods to reconstruct the equilibrium-line altitude (ELA) of the Die Shan paleo-ice cap on the northeastern Tibetan Plateau, and to infer past temperature for ice maximum positions believed to be mid-MIS 3 in age, based on regional correlation. Geomorphic ELA reconstructions combined with an energy and mass balance model yield a paleo-ELA of 4117±31 m asl (786 m lower than present) with temperature depressions of 3.8 to ~4.6°C compared to the present. This is less than the LGM reconstruction of temperature depression inferred from other climatic proxy records on the Tibetan Plateau and suggests that the LLGM glacial advance was a product of lower temperatures and slightly reduced precipitation compared to present, whereas the LGM was a more restricted advance in which much colder conditions were combined with much lower precipitation.